O3–NOy photochemistry in boundary layer polluted plumes: insights from the MEGAPOLI (Paris), ChArMEx/SAFMED (North West Mediterranean) and DACCIWA (southern West Africa) aircraft campaigns. Issue 4 (12th May 2022) - Thera, B.; Dominutti, P.; Colomb, A.; Michoud, V.; Doussin, J.-F.; Beekmann, M.; Dulac, F.; Sartelet, K.; Borbon, A.
Abstract : The ozone–NO y photochemistry is investigated in contrasting polluted plumes explored with the Safire ATR 42 research aircraft during three summer field campaigns in the megacity Paris, the North West Mediterranean basin and southern West Africa. Abstract : The ozone–NO y photochemistry is explored in contrasting polluted plumes sampled with the Safire ATR 42 research aircraft during three summer field international campaigns in the megacity Paris, the North West Mediterranean basin (WMB) and southern West Africa (SWA). Various metrics derived from the photostationary steady state (PSS) and the ozone production efficiency (OPE) are calculated from airborne observations. A new metric, the oxidant production rate normalized to carbon monoxide (PRO x ), is introduced and quantified as a function of the processing time of the plume. In most of the polluted plumes, it is found that the Leighton ratio ( Φ ) characterizing the equilibrium between O3 and NO x is, on average, within the PSS range ([1 ± 0.32]) or greater. The positive dependence of O x to NO usually indicates a VOC-sensitive regime inside the plumes with some exceptions. In Paris, under oceanic westerly winds, and during DACCIWA, the plumes show a rural-like chemistry behaviour at moderate NO x levels (NO x -sensitive). Intense and frequent rapid changes in J (NO2 ), NO and NO2 explain the deviations from the PSS. The OPE for Paris plume suggests that the VOC-sensitive regime extends far beyond the urban plume. The mean ozone production is higher downwind of Paris (30 ppb h −1 on average) compared to SWA (20 ppb h −1 ) and WMB (6 ppb h −1 ). PRO x values vary between 0 (no oxidant production) and 0.27 ppb[Ox] ppb[CO] −1 h −1 . The determined uncertainty on the Leighton ratio value could affect the differences in the estimation of the photochemical oxidant production by PO3 and PRO x. The emissions of CO along the flight path and the presence of vegetation and high humidity levels might shape the oxidant production depending on the explored environment . While limited in number, PRO x values set a benchmark for future photochemical studies to compare with: Paris as representative of an anthropogenic urban plume and WMB as representative of a biogenic continental plume.